2012
DOI: 10.1051/0004-6361/201219547
|View full text |Cite
|
Sign up to set email alerts
|

The star formation and chemical evolution history of the Fornax dwarf spheroidal galaxy

Abstract: We present deep photometry in the B, V and I filters from CTIO/MOSAIC for about 270 000 stars in the Fornax dwarf spheroidal galaxy, out to a radius of r ell ≈ 0.8 degrees. By combining the accurately calibrated photometry with the spectroscopic metallicity distributions of individual red giant branch stars we obtain the detailed star formation and chemical evolution history of Fornax. Fornax is dominated by intermediate age (1−10 Gyr) stellar populations, but also includes ancient (10−14 Gyr), and young (≤1 G… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
155
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(169 citation statements)
references
References 71 publications
12
155
2
Order By: Relevance
“…For both Sculptor and Leo I the corresponding range is 1.0-6.0 × 10 6 M⊙. Observational estimates of stellar mass are ∼ 1.7-4.3 × 10 7 M⊙ for Fornax, ∼ 0.2 × 10 7 M⊙ for Sculptor and ∼ 0.5 × 10 7 M⊙ for Leo I (Wolf et al 2010;McConnachie 2012;de Boer et al 2012).…”
Section: Selecting Simulated Analogues Of Real Dsphsmentioning
confidence: 93%
“…For both Sculptor and Leo I the corresponding range is 1.0-6.0 × 10 6 M⊙. Observational estimates of stellar mass are ∼ 1.7-4.3 × 10 7 M⊙ for Fornax, ∼ 0.2 × 10 7 M⊙ for Sculptor and ∼ 0.5 × 10 7 M⊙ for Leo I (Wolf et al 2010;McConnachie 2012;de Boer et al 2012).…”
Section: Selecting Simulated Analogues Of Real Dsphsmentioning
confidence: 93%
“…LG dSphs (Tolstoy et al 2004;Battaglia et al 2006Battaglia et al , 2011de Boer et al 2012a;de Boer et al 2012b). Furthermore, recent wide field photometric studies have found signs of extra-tidal stars, suggesting that Carina likely experienced tidal encounters, which could be responsible for the episodic SFH (Battaglia et al 2012;McMonigal et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…They are not currently forming stars and show prominent old stellar populations, but their star formation histories (SFHs) are not uniformly old (see the recent reviews of Tolstoy et al 2009;Weisz et al 2014). Indeed, dSphs show a wide variety of SFHs; from systems that essentially completed forming their stars ∼ 10 Gyr ago, like Cetus and Draco (Monelli et al 2010;Aparicio et al 2001) to others where star formation was sustained over a long time and ceased only as recently as 6 Gyr ago (e.g., Leo II, Dolphin 2002) or even < 1 Gyr ago (e.g., Fornax, Stetson et al 1998;Saviane et al 2000;Battaglia et al 2006;de Boer et al 2012, and references therein).…”
Section: Introductionmentioning
confidence: 99%